KEDUDUKAN ANAK LUAR KAWIN: Analisis Putusan Mahkamah Konstitusi No. 46/PUU-VIII/2010 Tentang Uji Materi Terhadap Pasal 43 Ayat 1 UU No. 1 Tahun 1974 Tentang Perkawinan - Arifin, Muhammad (Ahkam: Jurnal Hukum Islam, 2017)
This article discusses the right of children as the result of non marital relationship based on the Indonesian Constitution Court interpretation. The analysis is conducted using normative juridical approach. The finding shows that there are two groups of children. The first, the children still have the rights exactly similar to those who are born in a marital relationship such as the right of living expenditure, the right of marital guardian, the right of breast feeding, and the right of heredity. The second group of children do not receive the rights similar to the first group. They may not claim the right of living expenditure, the right of marital guardian, the right of breast feeding, and the right of heredity from their parents. Their relationship with their biological parents is just the same as the relationship with common people.Keywords: Anak Luar Nikah, Putusan MK, UU No. 1/1974